MENINGKATKAN KEDISIPLINAN BELAJAR SISWA DALAM PEMBELAJARAN TEMATIK DENGAN MENGGUNAKAN REWARD STICKER PICTURE PADA SISWA DI SEKOLAH DASAR - Yudhi Novriadi; Yanti Yandri Kusuma; Putri Hana Pebriana (Universitas Negeri Surabaya, 2022)
This research is motivated by the low discipline of the student learning process in the fourth grade thematic learning at SDN 004 Bangkinang Kota. This study aims to improve student learning discipline by using Reward Sticker Pictures in class IV learning at SDN 004 Bangkinang Kota. This type of research is classroom action research (CAR). This research was carried out in 2 cycles and each cycle was carried out in two meetings. The subjects of this study were the fourth grade students of SDN 004 Bangkinang Kota, totaling 12 students with 4 male students and 8 female students. Data collection techniques used in the study were observation and documentation techniques. Based on the results of the study, it can be concluded that in the first cycle it is still quite adequate with an average of 70.1%. Student learning outcomes in cycle II are classified as good with an average of 89.5%. Thus, it can be concluded that using Reward Sticker Picture can improve student learning discipline in grade IV SDN 004 Bangkinang Kota